Characterization and sequence of the promoter region of the human epidermal growth factor receptor gene. - Ishii, S (1985)
The promoter region of the epidermal growth factor (EGF) receptor has been identified by in vitro transcription using EGF receptor genomic DNA fragments as template and by primer extension and nuclease S1 mapping using EGF receptor mRNA. Six transcriptional start sites were identified. DNA sequence analysis shows that the promoter region contains neither a "TATA box" nor a "CAAT box," has an extremely high G+C content (88%), and contains five CCGCCC repeats and four (TCC)TCCTCCTCC repeats. This promoter region is situated close to or within a DNase I-hypersensitive site in A431 human epidermoid carcinoma cells, which overproduce the EGF receptor. The EGF receptor gene promoter has some resemblance to the promoter of the hydroxymethylglutaryl-CoA reductase gene and the early promoter of simian virus 40. This similarity may offer a clue to the mechanism by which the receptor gene is regulated.